2021
DOI: 10.1073/pnas.2111477118
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinetics of SARS-CoV-2 infection and its relationship with a person’s infectiousness

Abstract: The within-host viral kinetics of SARS-CoV-2 infection and how they relate to a person’s infectiousness are not well understood. This limits our ability to quantify the impact of interventions on viral transmission. Here, we develop viral dynamic models of SARS-CoV-2 infection and fit them to data to estimate key within-host parameters such as the infected cell half-life and the within-host reproductive number. We then develop a model linking viral load (VL) to infectiousness and show a person’s infectiousness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
210
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(268 citation statements)
references
References 57 publications
20
210
0
Order By: Relevance
“…We assumed that the two quantities can be described by a density dependent function ( Eq. 7 in Materials and Methods ) as in [8, 13]. Through fitting this function to the population ( R u , V u ) data in the three groups (taking into consideration the presence of censored data, see Materials and Methods for full explanation), we found that the level of infectious viruses increases sub-linearly with increases in viral RNA, with the same exponent h=0.6 in all three groups.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We assumed that the two quantities can be described by a density dependent function ( Eq. 7 in Materials and Methods ) as in [8, 13]. Through fitting this function to the population ( R u , V u ) data in the three groups (taking into consideration the presence of censored data, see Materials and Methods for full explanation), we found that the level of infectious viruses increases sub-linearly with increases in viral RNA, with the same exponent h=0.6 in all three groups.…”
Section: Resultsmentioning
confidence: 94%
“…Over the last two years, within-host mathematical models developed for influenza and other respiratory infections have been modified for SARS-CoV-2 infections [10, 11, 13, 15, 23, 31]. These models divided total viral titers into infectious and non-infectious particles [7, 27], fitted their sum to total RNA values measured by PCR (used as a proxy for total virus load) and used the results to determine the mechanisms of viral expansion and loss.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, second precursor cells differentiate into effector cells at the same per capita rate q and are cleared at rate δ E . Other models have described withinhost viral loads differently, including by using multiple compartments and without an adaptive immune response [51][52][53].…”
Section: Data-validated Sars-cov-2 Within-host Model Captures Viral L...mentioning
confidence: 99%
“…We chose not to fit mechanistic models (e.g. [15]) as the goal was not explain the biology underlying viral clearance but to provide a robust method from which to infer summary statistics for virological clinical trial endpoints.…”
Section: Model Of Viral Clearance Dynamicsmentioning
confidence: 99%